(untitled) (Journal of the College of Basic Education, 2023)
Fate ordained that the Arab nation be a nation of poetry, and poetry in particular is a first flame in everyA turn, and when the ages were dark (and in the darkness of the nineteenth century, literary lights shoneAnd poetic confirming the pangs of national literature in the Arab countries in general, and in Iraq, the country of Arabism.and Arab civilization in particular), (1) Poetry was always a race in the struggle and expression of the concerns ofthe nation to rise from a slumber or straighten up after a setback, and at the same time it was impossible forPoetry, which lived through a period of decline and stagnation in the past centuries, since weakness began to creep in.the entity of the Arab nation at the end of the Abbasid state, and the Arabs began to lose their independence andThe nationalist in deterioration and dissolution, to express the necessity of the national feeling of the nation and did not remove thatdispossessed, except when its existence is threatened by many factors that want to obliterate its identity and demolishThe elements of resistance stirred in the spirit, mind and body of the Arab nation, and took the path ofThe struggle to get out of the impasse, confront the danger, and confront the enemies’ attempts to endits existence. And this poetry began to appear with an important group of nineteenth-century poets.Poets who embodied through their positions against the ruling authorities the depth of their national consciousnessand the authenticity of their belonging to the Arab nation, those positions that call for the rise of the Arabs and the struggle againstFor independence and liberation and stands at the top of this constellation. The poet Abdul-Ghani Al-Jamil.